1989
DOI: 10.1210/jcem-69-4-896
|View full text |Cite
|
Sign up to set email alerts
|

The New Aromatase Inhibitor CGS-16949A SuppressesAldosterone and Cortisol Production by Human Adrenal Cellsin vitro

Abstract: CGS-16949A is a new orally active nonsteroidal aromatase inhibitor which is more than 100-fold more potent than aminoglutethimide. This compound is an imidazole derivative, and therefore, its possible effect on cytochrome P-450-dependent enzyme activities in the adrenal gland was evaluated. In vitro investigations with dispersed normal and hyperplastic human adrenocortical cells showed that CGS-16949A at 10(-7)-10(-6) M is a potent 11 beta-hydroxylase inhibitor, which inhibits ACTH-stimulated cortisol release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The inhibitory activities of the compounds were determined in V79 MZh cells expressing either human CYP11B2 or CYP11B1. 10 ability to reduce corticoid formation in vitro 29 and in vivo, 30 was used as a reference (CYP11B2, IC 50 ) 1 nM; CYP11B1, IC 50 ) 10 nM).…”
Section: Chemistrymentioning
confidence: 99%
“…The inhibitory activities of the compounds were determined in V79 MZh cells expressing either human CYP11B2 or CYP11B1. 10 ability to reduce corticoid formation in vitro 29 and in vivo, 30 was used as a reference (CYP11B2, IC 50 ) 1 nM; CYP11B1, IC 50 ) 10 nM).…”
Section: Chemistrymentioning
confidence: 99%
“…7 Aldosterone synthase inhibition has, thus, emerged as a new therapeutic option aimed at decreasing hormone concentrations in both plasma and tissues, thus reducing both its MR receptor-dependent and -independent effects 1,6,7 at the level of renal epithelial cells and cardiac and vascular target organs. Fadrozole, an aromatase inhibitor with inhibitory properties against aldosterone synthase, 18,19 and its dextroenantiomer FAD286 have been experimentally tested preclinically, 20 -24 but this potential therapeutic approach has never been investigated in patients.…”
mentioning
confidence: 99%
“…Early investigation showed that it was not as potent an aromatase inhibitor as expected, and was certainly less potent than the subsequently developed letrozole, anastrozole and exemestane [28][29][30]. Furthermore, it was not specific, as it has an inhibitory effect on aldosterone synthesis [31]. At a daily dose of 16 mg, fadrozole induced a significant increase in the blood 18-hydroxycorticosterone/aldosterone ratio, consistent with an aldosterone-synthase inhibition [32].…”
Section: Introductionmentioning
confidence: 93%